Impacts of population growth and economic development on food security in low-income and middle-income countries - Miladinov, Goran (Frontiers in Human Dynamics, 2023)
Attention to addressing undernourishment in low-and middle-income countries has expanded notably since the beginning of the 21st century. Population growth increases the overall demand for food, while income growth affects consumption patterns. Using annual aggregate data from the World Bank in 2001-2020 and econometric approaches, this research investigates the changes in the growth rates in rural and urban populations and GDP per capita and the prevalence of undernourishment as % of the population in low-income countries, lower-middle-income countries, and upper-middle income countries. The main goal of the study is to convey a deeper understanding by quantifying the impacts of rural and urban population growth as well as GDP per capita growth on the prevalence of undernourishment. The robust regression models showed that the prevalence of undernourishment in these countries was strongly associated with rural and urban population growth. A positive impact of rural population growth on undernutrition was found in all three groups of countries, with the most significant positive effects found in upper-middle-income countries. The negative effect of urban population growth on undernourishment was largest for the upper middle-income countries. Furthermore, fully modified ordinary least squares results revealed that the changes in the prevalence of undernourishment are mostly associated with long-term changes in the rural and urban population growth. The Difference in Difference (DiD) estimation confirmed only the causal effect of rural population growth on the prevalence of undernourishment in the panel of these countries. The findings of this study have both methodological and policy implications. Keywords: robust least square; low-income countries, lower-middle-income countries, upper-middle-income countries, GDP per capita growth, undernourishment, FMOLS, DiD